Synthesis and alpha ‐ inhibitory activity of lupane type С2‐benzylidene‐ triterpenoids. Issue 5 (22nd October 2021) - Khusnutdinova, Elmira F.; Ha, Nguyen Thi Thu; Giniyatullina, Gulnara V.; Anh, Le Thi Tu; Poptsov, Alexander I.; Kazakova, Oxana B.
Abstract: A series of novel and previously synthesized lupane type С2‐benzylidene derivatives was evaluated on α ‐glucosidase enzyme inhibition. Most of the tested compounds exhibited significantly better activity (1.8‐700 times higher) than the standard drug acarbose. The structure‐activity relationship indicated that the type of benzylidene moiety and C28‐substituent of lupane core plays an important influence on the activity. Methyl 2‐furfurylidene betulonate, m ‐iodo‐benzylidene betulonic acid and 3‐pyridinylideno‐betulonic acid hydrazide have been founded as effective α ‐glucosidase inhibitors and deserve further attention.